Review of Koume’s World: The Life and Work of a Samurai Woman Before and After the Meiji Restoration by Simon Partner, New York: Columbia University Press, 2024. Xx + 289 - Wert, Michael (Silva Iaponicarum, 2024)
Review of Koume’s World: The Life and Work of a Samurai Woman Before and After the Meiji Restoration by Simon Partner, New York: Columbia University Press, 2024. Xx + 289